2013
DOI: 10.1021/am4028857
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Self Assembled Sodium Oleate Monolayer on Mild Steel and Its Corrosion Inhibition Behavior in Saline water

Abstract: A self assembled monolayer (SAM) of sodium oleate was generated on mild steel by the dip coating method. Formation of the SAM on mild steel was examined using Infrared Reflection Absorption Spectroscopy (IRRAS) and contact angle measurements. The chemical and anticorrosive properties of the SAM were analyzed using different techniques. IRRAS and water contact angle data revealed the crystallinity and chemical stability of the SAM modified mild steel. The electrochemical measurements showed that the mild steel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…In recent years, enormous efforts have been devoted to finding efficient corrosion inhibitors. [3][4][5] Most of the corrosion inhibitors investigated are heterocyclic organic compounds containing electronegative functional groups with π-electron systems and heteroatoms like sulfur, nitrogen, oxygen as well as aromatic rings in their structures. [6][7][8] It is generally believed that these molecules adsorb on the metal surface by displacing water molecules on the surface and forming a protective film.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, enormous efforts have been devoted to finding efficient corrosion inhibitors. [3][4][5] Most of the corrosion inhibitors investigated are heterocyclic organic compounds containing electronegative functional groups with π-electron systems and heteroatoms like sulfur, nitrogen, oxygen as well as aromatic rings in their structures. [6][7][8] It is generally believed that these molecules adsorb on the metal surface by displacing water molecules on the surface and forming a protective film.…”
Section: Introductionmentioning
confidence: 99%
“…4). For SO, it has been reported that monolayers of this surfactant on steel can reduce the rate of corrosion (measured as current density) by almost one order of magnitude in acid media [48]. This effect has been linked to the formation of hydrophobic coatings on the surface of iron that prevent the transport of species involved in the redox reaction.…”
Section: Effect Of Surfactant Adsorption On Degradation Of Rb5mentioning
confidence: 99%
“…this is due to the formation of soluble corrosive product and lack of formation of the passive film on the substrate surface [27]. In the presence of Santolina, the steel shows a more positive potential by adsorbtion on the surface that it helps to slow the corrosion reaction.…”
Section: Open Circuit Potential Versus Timementioning
confidence: 99%